Evaluation of ornamental value and adaptability of eight varieties of crape myrtle with color leaves - WANG Ying; LI Yujuan; TAN Feng; GUO Cong (浙江大学学报. 农业与生命科学版)
With the analytic hierarchy process (AHP), the ornamental value, ecological adaptability and growth characteristics of eight varieties of crape myrtle with color leaves were evaluated comprehensively, which helping to select out the best varieties adapting to Nantong area in Jiangsu Province. The results showed that the weight value of leaf color is the largest, followed by flower color, which are important indexes to evaluate the ornamental value of crape myrtle. The weight values of overall form and fruit were auxiliary indexes of ornamental evaluation. Resistance to pests and diseases and wet resistance were important indexes to evaluate the adaptability of crape myrtle. Growth rate was also a key factor for successful introduction. Through the comprehensive analysis model, three crape myrtles with color leaves belonged to grade Ⅰ level, including ‘Blush’, ‘Red Hot’ and ‘Crimson Red’, among which ‘Blush’ was especially the best of all.